Severe illness getting noticed sooner – SIGNS-for-Kids: developing an illness recognition tool to connect home and hospital. Issue 4 (27th November 2019) - Gilleland, Jonathan; Bayfield, David; Bayliss, Ann; Dryden-Palmer, Karen; Fawcett-Arsenault, Joelle; Gordon, Michelle; Hartfield, Dawn; Iacolucci, Anthony; Jones, Melissa; Ladouceur, Lisa; McNamara, Martin; Middaugh, Kristen; et al.
Abstract : Background: Delays to definitive treatment for time-sensitive acute paediatric illnesses continue to be a cause of death and disability in the Canadian healthcare system. Our aim was to develop the SIGNS-for-Kids illness recognition tool to empower parents and other community caregivers to recognise the signs and symptoms of severe illness in infants and children. The goal of the tool is improved detection and reduced time to treatment of acute conditions that require emergent medical attention. Methods: A single-day consensus workshop consisting of a 17-member panel of parents and multidisciplinary healthcare experts with content expertise and/or experience managing children with severe acute illnesses was held. An a priori agreement of ≥85% was planned for the final iteration SIGNS-for-Kids tool elements by the end of the workshop. Results: One hundred percent consensus was achieved on a five-item tool distilled from 20 initial items at the beginning of the consensus workshop. The final items included four child-based items consisting of: (1) behaviour, (2) breathing, (3) skin, and (4) fluids, and one context-based item and (5) response to rescue treatments. Conclusions: Specific cues of urgent child illness were identified as part of this initial development phase. These cues were integrated into a comprehensive tool designed for parents and other lay caregivers to recognise the signs of serious acute illness and initiate medical attention in an undifferentiated population of infants and children. Future validation and optimisation of the tool are planned.